Talak Dalam Perbandingan Madzhab - Nasikhin, Durotun; Nurcholis, Mujio; Sucipto, Imam (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2023)
Abstract: Divorce occurs after the marriage contract. Divorce is often undersstimed by society because talak is seen as a symbol of failure in marriage. Many people are confused about the dynamics of the issue regarding under certain circumtances the husband divorcing, whether his divorce is considered legal or illegal. From these various, conditions, laws and types of divorce will be discussed based on the opinion of jurists from various schoolsn of thought. The research method is descriptive based on literature review with primary data in the form of Bidayatul Mujtahid, Fiqih Islam Wa Adillatuhu, Fathul Qarib and other supporting scientific works. The original law of divorce is permissible but can be obligatory, sunnah, makruh and unlawful depending on the backround. There are all kinds of divorces sharih kinayah, sunni bid’i, raj’i ba’in and the dynamics that accompany it. It is hoped that it can help understand of the jurists regarding the point of view in differences of opinion as well as what are the terms and the law of divorces and its distribution.Keyword: Merriage, Divorce, Opinion, Madzhab Abstrak: Talak terjadi setelah adanya akad pernikahan. Perceraian sering dipandang sebelah mata oleh masyarakat karena talak dianggap sebagai simbol kegagalan dalam berumah tangga. Banyak orang yang kebingungan dalam berbagai dinamika persoalan mengenai dalam kondisi tertentu suami menjatuhkan talak, apakah talaknya dianggap sah atau tidak sah. Dari berbagai persoalan itu akan dibahas syarat, hukum dan macam-macam talak berdasarkan pendapat para ahli fiqih dari berbagai madzhab. Metode penelitiannya bersifat deskriptif berdasar kajian pustaka dengan data primernya berupa Bidayatul Mujtahid, Fiqh Islam Wa Adillatuhu, Fathul Qarib dan karya ilmiah penunjang lainnya. Hukum asal talak adalah boleh namun bisa menjadi wajib, sunnah, makruh dan haram tergantung yang melatarbelakanginya. Macam talak ada sharih kinayah, sunni bid’i, raj’i ba’in serta dinamika persoalan yang menyertainya. Diharapkan bisa membantu memahami berbagai argumentasi para fuqaha mengenai cara pandang dalam perbedaan pendapat juga apa saja syarat dan hukum talak serta pembagiannya.Kata kunci: Nikah, Cerai, Pendapat, Madzhab